Chemical composition, embryo anatomy and viability by tetrazolium test of pyrenes of Euterpe edulis Mart - Iossi, Emerson [UNESP]; Môro, Fabíola Vitti [UNESP]; Ferrari, Roseli Aparecida; Barbosa, Rafael Marani; Vieira, Roberval Daiton [UNESP] (Revista Brasileira de Ciencias Agrarias, 2016)
The advancement of knowledge and technologies for production, quality assessment and conservation of seeds of E. edulis is a need imposed by the high demand for this plants. Information on biometry, chemical composition and anatomy of seeds and seedlings give basis for the marking of future studies. The objectives of this study were to describe the biometrics and chemical composition of fruits and seeds, the anatomy of embryos; assess the viability of seeds by tetrazolium and classify the seeds of Euterpe edulis Mart. as for desiccation and storage tolerance. Seeds were analyzed for biometrics, water content, chemical composition, germination and seedling emergence. For the tetrazolium test, embryonic axes were immersed in a solution at 40°C for one, two, four and six hours. As for desiccation tolerance, seeds with water content of 45.7, 12 and 5% were evaluated for germination. E. edulis seeds have 83.1% carbohydrates and recalcitrant behavior, and the tetrazolium test conducted at 40°C in solution at 0.2% concentration for two hours proved to be adequate to estimate seed viability.
Keywords: Anatomy; Arecaceae; Biometry; Germination; Viability